Nutritional status, anemia status and application of the Mentzer index on complete blood examination results of students - Pratama, Yanasta Yudo; Ratnaningsih, Tri; Arijadi, Desi; Adnan, Muhammad Luthfi; Widyasari, Vita; Tristifany, Annisa; Santoso, Griselda Elisse; Usman, Muhammad Alvin Ramadhan; Miftahurrahmi, Rofifah (Universitas 'Aisyiyah Yogyakarta, 2023)
Thalassemia is a disease that attacks the hemoglobin gene, causing disturbances in erythropoiesis. Anemia is a condition in which the hemoglobin (Hb) concentration and the number of erythrocytes are below normal limits. The high number of anemia and thalassemia causes the need for early detection in order to prevent adverse effects in the future. Research objectives: to determine nutritional status, anemia status, and application of the Mentzer Index for SMK Muhammadiyah II Moyudan students. Methods: This study is a descriptive study with a cross-sectional design. The research subjects were first graders at SMK Muhammadiyah 2 Moyudan. Venous blood samples were examined at the Clinical Pathology Laboratory of FK-KMK UGM using the Sysmex XN-1000 tool on November 25, 2021. Data analysis used IBM SPSS Version 26 and Microsoft Office 365. Results: A total of 53 subjects participated in this study. A total of 47 (89%) respondents had normal hemoglobin values, and 6 (11%) respondents suffered from anemia. 31 (58.5%) respondents have normal nutrition, 15 (28%) respondents have less nutrition, 7 (13%) have excess nutrition, and 29 (54.7%) respondents have normal status. A total of 2 (3.8%) respondents showed Thalassemia. Conclusion: There are two students of SMK Muhammadiyah 2 Moyudan diagnosed with thalassemia and five students diagnosed with anemia. No statistically significant difference exists between Anemia Status in Adolescents at SMK Muhammadiyah 2 Moyudan and Nutritional Status. Further study is needed in wider and more diverse populations to analyze the influence of nutritional conditions on anemia in adolescents.